A milkfat globule membrane-inspired approach for encapsulation of emulsion oil droplets. (April 2017) - Livney, Yoav D.; Ruimy, Emmanuelle; Ye, Aiqian M.; Zhu, Xiangqian; Singh, Harjinder
Abstract: The milkfat globule membrane (MFGM) is a fascinating tri-layer structure of phospholipids and proteins naturally encapsulating milkfat globules. Herein, we aimed at introducing a novel approach, inspired by the MFGM structure, for encapsulating emulsion oil droplets. To obtain a prototype, we formed a cationic oil-in-water (O/W) emulsion using lactoferrin (LF), as the primary emulsifier. Excess unadsorbed LF was washed away, and the washed emulsion (WE) was concentrated to 73.4 ± 1.0% oil (zeta potential +38.2 ± 1.3 mV). Milk-phospholipid concentrate in ethanol was dried in a flask filled with glass beads. WE was added and swirled with the beads. The obtained "coated emulsion" (CE) had a zeta potential of −26.1 ± 1.1 mV, evidencing droplet surface coverage with phospholipids. Confocal microscopy showed WE droplets were covered with protein only, while CE droplets were coated with both LF and phospholipids. Transmission electron microscope (TEM) images of the WE showed a protein monolayer on the droplet surface, while in the CE, oil droplets were partly coated with lamellar phospholipid structures, adsorbed onto the protein layer. In contrast, attempting to coat an anionic whey protein isolate (WPI) based primary emulsion with the phospholipids, resulted in competitive displacement of the WPI from the oil surface and partial coalescence. A prototype of a MFGM-resembling lamellar phospholipid structure coating emulsion droplets, has been obtained and characterized here for the first time. Graphical abstract: Highlights: The milkfat globule membrane (MFGM) is a tri-layer phospholipid-protein structure. We report a novel microencapsulation approach, inspired by the MFGM structure. Lactoferrin (LF) emulsified O/W emulsion was coated with phospholipid lamellae. Systems were studied by light scattering, ζ-potential, confocal microscopy and TEM. A prototype of phospholipid lamellae nanocoated oil droplets was obtained.